(untitled) (English Language and Literature (JELL), 2026)
The study aims to determine the phonemic-phonological and lexical variations of the Batak Toba language as spoken in Tapanuli Tengah and Tapanuli Utara. The research focuses on identifying linguistic differences between two sub-dialects that share the same linguistic origin but develop distinct features due to geographical and social factors. The study employed descriptive qualitative method. The data were collected through interviews with ten native speakers selected based on the NORMS criteria, using Swadesh list of 207 basic lexical items and 54 additional daily vocabulary. The data were analyzed by classifying and comparing phonological and lexical forms across the two sub-dialects. The findings indicate that 24 phonemic-phonological variations, including 3 initial consonant shifts, 3 initial dropping, 5 gemination, 2 palatalization, 1 initial vowel change, 2 diphtongization, 7 vowel shift, and 1 nasal variation, as well as 73 lexical variations in which different words express the same meanings. These findings show that geographical and social factors play a significant role in shaping dialectal variation within the Batak Toba language.